Strengthening Character Education Through The Local Cultural Values Of The Five Palambang Of Semende South Sumatra As A Provision For The Generation Of Alpha (Gen A) - Septiaseh, Dwi; Haniah, Munnal; Pratama, Galih Cahya; Munfariqoh, Aqidatul (Directorate of Research and Community Service, Universitas Negeri Yogyakarta, 2025)
Generation Alpha has unique characteristics from previous generations. This generation grows up surrounded by technology and easily accessible information. Therefore, it is important to equip them with strong character education in order to become a resilient and noble generation. This research aims to find out the values of Lima Palembang Semende that are internalised and manifested in the daily behaviour of individuals, thus providing the formation and strengthening of the Alpha generation's character. The method in this research is descriptive qualitative. Data collection from structured interviews, documentation and literature review related to cultural values in character building with Semende customs. Miles & Huberman data collection technique with 4 stages, namely data collection, data reduction, data display and conclusion drawing. The results showed that the local cultural values of the Five Palambang of Semende Custom (jale, axe, kujur, guji and tebat) can shape and strengthen character education such as honesty, trustworthiness, mutual cooperation, deliberation to strengthen the character of the Alpha generation. These values can be instilled in the Alpha Generation through various activities that are appropriate to their age and development. Explicitly, these findings provide an interaction between the five symbols of Semende custom with the alpha generation who are familiar with digital technology such as reinterpretation of virtual reality technology by creating game characters with cultural and moral values such as justice, gotong royong. Furthermore, cultural hybridisation, where the alpha generation can combine traditional values with modern lifestyles. This research provides recommendations for stakeholders in education, culture, and society to work together in preserving the local cultural values of the Five Palembang Adat Semende with digital technology has great potential to strengthen the character and moral education of the Alpha generation.